2012
DOI: 10.1073/pnas.1212303109
|View full text |Cite
|
Sign up to set email alerts
|

An original mode of symbiosis in open ocean plankton

Abstract: International audienceSymbiotic relationships are widespread in nature and are fundamental for ecosystem functioning and the evolution of biodiversity. In marine environments, photosymbiosis with microalgae is best known for sustaining benthic coral reef ecosystems. Despite the importance of oceanic microbiota in global ecology and biogeochemical cycles, symbioses are poorly characterized in open ocean plankton. Here, we describe a widespread symbiotic association between Acantharia biomineralizing microorgani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
160
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 135 publications
(167 citation statements)
references
References 50 publications
4
160
0
3
Order By: Relevance
“…Until now, all of the sequences affiliated to P. jahnii and P. cordata have been retrieved from latitudes between 10 and 45°. A recent study on the phylogeny of the symbiotic relationship between Phaeocystis and Acantharia demonstrated that genetic distances of symbiont Phaeocystis were significantly correlated to its biogeography, but had no relationship with the host taxonomy (Decelle et al 2012). Overall, our results are consistent with previous studies showing that species of Phaeocystis occurring in polar and non-polar areas are distinct (Schoemann et al 2005, Decelle et al 2012.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Until now, all of the sequences affiliated to P. jahnii and P. cordata have been retrieved from latitudes between 10 and 45°. A recent study on the phylogeny of the symbiotic relationship between Phaeocystis and Acantharia demonstrated that genetic distances of symbiont Phaeocystis were significantly correlated to its biogeography, but had no relationship with the host taxonomy (Decelle et al 2012). Overall, our results are consistent with previous studies showing that species of Phaeocystis occurring in polar and non-polar areas are distinct (Schoemann et al 2005, Decelle et al 2012.…”
Section: Discussionsupporting
confidence: 83%
“…A recent study on the phylogeny of the symbiotic relationship between Phaeocystis and Acantharia demonstrated that genetic distances of symbiont Phaeocystis were significantly correlated to its biogeography, but had no relationship with the host taxonomy (Decelle et al 2012). Overall, our results are consistent with previous studies showing that species of Phaeocystis occurring in polar and non-polar areas are distinct (Schoemann et al 2005, Decelle et al 2012. Few studies have reported blooms of P. jahnii and P. cordata, which may be due to their small size, or may indicate that they cannot form, or seldom form, colonies in the natural environment (Zingone et al 1999, Medlin & Zingone 2007.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reads of genotype 2 also displayed negative correlations with some nutrients (NO 2 , PO 4 , Si), whereas those of genotype 1 had positive correlations with the depth of the deep chlorophyll maximum. Thus, the correlation patterns between the host, its symbiont and their abiotic environment clearly indicate that the symbiotic partnership predominantly occurs in oligotrophic conditions (typically characterized by deep chlorophyll maximum and low chlorophyll and nutrient concentrations), mirroring the ecology of other known planktonic photosymbioses (Shaked and de Vargas, 2006;Stoecker et al, 2009;Decelle et al, 2012). More specifically, we note that genotype 2 positively correlated with salinity, very likely because of its prevalence in the Mediterranean Sea.…”
Section: Phylogenetic Identification Of the Microalgal Symbiontmentioning
confidence: 82%
“…Many hosts build mineral skeletons of calcium carbonate, silica or strontium sulfate, hence contributing to the biogeochemical cycles of these elements (Bernstein et al, 1987). For instance, the rhizarian Radiolaria and Foraminifera are known to develop obligate photosymbioses in surface waters with diverse eukaryotic microalgae, such as photosynthetic dinoflagellates (for example, Brandtodinium, Pelagodinium) and haptophytes (for example, Phaeocystis) (Gast and Caron, 2001;Shaked and de Vargas, 2006;Decelle et al, 2012;Probert et al, 2014). Some heterotrophic dinoflagellates have also been found to host prasinophyte (Sweeney, 1976) or pelagophyte (Daugbjerg et al, 2013) microalgae.…”
Section: Introductionmentioning
confidence: 99%